A National Survey of Teachers on Antiretroviral Therapy in Malawi: Access, Retention in Therapy and Survival - Makombe, Simon D. (Public Library of Science, 2007)
BACKGROUND: HIV/AIDS is having a devastating effect on the education sector in sub-Saharan Africa. A national survey was conducted in all public sector and private sector facilities in Malawi providing antiretroviral therapy (ART) to determine the uptake of ART by teachers and their outcomes while on treatment. METHODOLOGY/PRINCIPAL FINDINGS: A retrospective cohort study was carried out based on patient follow-up records from ART Registers and treatment master cards in all 138 ART clinics in Malawi; observations were censored on September 30(th) 2006. By this date, Malawi's 102 public sector and 36 private sector ART clinics had registered a total of 72,328 patients for treatment. Of these, 2,643 (3.7%) were teachers. Adjusting for double-registration caused by clinic transfers, it is estimated that 2,380 individual teachers had ever accessed ART. There were 15% of teachers starting ART in WHO clinical stage 1 or 2 with a CD4-lymphocyte count of ≤250/mm(3) and 85% starting in stage 3 or 4. By 30(th) September 2006, 1,850 teachers were alive on ART (3.5% of all teachers in Malawi). The probability of being alive on ART at 6-months, 12-months, 18-months and 24-months after treatment initiation was 84%, 79%, 75% and 73% respectively. Retention in treatment was better for women (adjusted HR = 1.8) and in those starting ART in WHO Clinical Stage 1 and 2 (adjusted HR = 1.8). CONCLUSION/SIGNIFICANCE: Rapid scale up of ART has allowed 2,380 HIV-positive teachers to access life-prolonging treatment. There is evidence that this intervention can help to mitigate some of the shortages of teaching personnel in resource-poor countries affected by a generalised HIV epidemic.